THE INFLUENCE OF FAMILY COMMUNICATION PATTERNS ON THE INDEPENDENCE OF CHILDREN WITH DISABILITIES - Juli Astutik; Budi Suprapto; Zaenal Abidin; Haryanto Haryanto (Social Welfare Study Program, 2024)
Abstract. This study aims to explore three key aspects: 1) family communication patterns with children with disabilities, 2) the level of independence of children with disabilities, and 3) the relationship between family communication patterns and the level of independence of children with disabilities in Ngawonggo Village, Tajinan District, Malang City. Every child, including those with disabilities, has the right to a decent life. The family is crucial for a child's growth and development, making the family's communication patterns significantly influential. Parents generally aspire for their children to develop well, and children with disabilities require special parental attention. The study employed a quantitative approach, targeting parents of children with disabilities through purposive sampling. Data collection involved questionnaires and interviews. Data analysis utilized product-moment correlation tests (r test) with a significance level of 0.05 to examine the relationship between family communication patterns and the independence of children with disabilities. Regression analysis was also conducted to predict changes in the independence of children based on communication patterns. Results indicated that: 1) family communication patterns with children with disabilities are mixed and flexible, adjusting to specific situations and conditions, 2) the level of independence of these children is 81.60%, and 3) there is a significant correlation (r count 0.816 > r tab 0.708) between family communication patterns and children's independence. The regression analysis suggested that improved communication patterns could enhance children's independence from an average of 74.916 to 87.1909. The study recommends that parents adopt a conversation model of family communication, recognizing the child's existence and providing opportunities for them to express and discuss their opinions and desires to foster greater independence.Keywords: Family communication patterns, independence, children with disabilities. Abstrak. Penelitian ini bertujuan untuk mengeksplorasi tiga aspek utama: 1) pola komunikasi keluarga dengan anak-anak penyandang disabilitas, 2) tingkat kemandirian anak-anak penyandang disabilitas, dan 3) hubungan antara pola komunikasi keluarga dengan tingkat kemandirian anak-anak penyandang disabilitas di Desa Ngawonggo, Kecamatan Tajinan, Kota Malang. Setiap anak, termasuk penyandang disabilitas, memiliki hak untuk hidup layak. Keluarga sangat penting untuk pertumbuhan dan perkembangan anak, sehingga pola komunikasi keluarga sangat berpengaruh. Orang tua umumnya ingin anak-anak mereka berkembang dengan baik, dan anak-anak penyandang disabilitas memerlukan perhatian khusus dari orang tua. Penelitian ini menggunakan pendekatan kuantitatif, menargetkan orang tua dari anak-anak penyandang disabilitas melalui sampel purposif. Pengumpulan data dilakukan dengan kuesioner dan wawancara. Analisis data menggunakan uji korelasi produk momen (uji r) dengan tingkat signifikansi 0,05 untuk menguji hubungan antara pola komunikasi keluarga dengan kemandirian anak-anak penyandang disabilitas. Analisis regresi juga dilakukan untuk memprediksi perubahan kemandirian anak berdasarkan pola komunikasi. Hasil penelitian menunjukkan bahwa: 1) pola komunikasi keluarga dengan anak-anak penyandang disabilitas bersifat campuran dan fleksibel, menyesuaikan dengan situasi dan kondisi tertentu, 2) tingkat kemandirian anak-anak penyandang disabilitas mencapai 81,60%, dan 3) terdapat korelasi signifikan (r hitung 0,816 > r tabel 0,708) antara pola komunikasi keluarga dengan kemandirian anak. Analisis regresi menunjukkan bahwa peningkatan pola komunikasi dapat meningkatkan kemandirian anak dari rata-rata 74,916 menjadi 87,1909. Penelitian ini merekomendasikan agar orang tua menerapkan model komunikasi keluarga berbasis percakapan, yang mengakui keberadaan anak dan memberikan kesempatan bagi mereka untuk mengekspresikan dan mendiskusikan pendapat serta keinginan mereka untuk meningkatkan kemandirian.Kata Kunci: Pola komunikasi keluarga, independensi, anak dengan disabilitas.